Inventory management model integrating lean and FLD to increase service level in an automotive retail: an empirical research in Perú - Galindo Alvarez, Katia Alessandra (2023)
The automotive industry has had large market penetration; however, there is not optimal retention of these customers, since there is a knowledge gap regarding loyalty strategies, which could impact the level of service offered. It is essential to have good inventory planning and a good distribution of the workshop to meet agreed dates. Also, correct execution of the service, which integrates quality control to avoid problems attributed to defects. This case study proposes a model that integrates Lean Manufacturing, Facility Layout Design, and ABC inventory management, intending to achieve an improvement in the current service. After the implementation of the model, on-time service was increased by 30.55%, reprocessed vehicles were reduced by 6.50%, labor efficiency was increased by 16.66%, open work orders were reduced by 13.79%, and transfer times were reduced by 20.90%.